1984
DOI: 10.1111/j.1600-0587.1984.tb01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of willow leaves in two Alberta Rocky Mountain streams

Abstract: Nylon bags of 3.5 mm and 0.25 mm mesh were used lo investigate the processing of Salix drummondiana Barratt leaves in two second order Alberta Rocky Mountain Creeks, Twin Creek and Cabin Creek. Micro‐organism processing and macroinvertebrate shredding of the leaves were significantly greater in Twin Creek where it was estimated that macroinvertebrate shredding was responsible for 45% of the weight loss. The decay coefficient (k = 0.0209) for the leaves in Twin Creek, the more typical Rocky Mountain stream, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…Weight losses from leaching recorded in this study are similar to those reported by Dawson (1976) of 15% after 5 days for S. viminalis and by Mutch & Davies (1984) of 23% after 17 days for S. drummondiana. After the initial leaching period, breakdown of leaves held in 3 mm mesh bags was the result of microbial decomposition and invertebrate feeding.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Weight losses from leaching recorded in this study are similar to those reported by Dawson (1976) of 15% after 5 days for S. viminalis and by Mutch & Davies (1984) of 23% after 17 days for S. drummondiana. After the initial leaching period, breakdown of leaves held in 3 mm mesh bags was the result of microbial decomposition and invertebrate feeding.…”
Section: Discussionsupporting
confidence: 79%
“…Microbial decomposition of leaves in the present study was much faster than losses feported by Mutch & Davies (1984) for leaves in 0.25 mm mesh bags in a typical Rocky Mountain stream in Alberta. This was despite the fact that Mutch & Davies (1984) attributed some leaf processing to the presence of small invertebrates which penetrated the fine mesh. In contrast, breakdown of leaves in 0.15 mm mesh bags was very rapid in a stream in New England, Australia (Pidgeon & Cairns 1981).…”
Section: Discussionmentioning
confidence: 82%
“…Pristine reference sites in the present study had breakdown rates (mean breakdown coefficient k ϭ 0.013 d Ϫ1 ) that were similar to those measured previously for willow litter in Rocky Mountain streams (Short et al 1980, Mutch andDavies 1984). Sites affected by mine drainage usually had lower rates.…”
Section: Rates Of Litter Breakdown In Streams Affected By Mine Drainagesupporting
confidence: 87%
“…Similarly, Nelson (2000) showed that the rate of litter breakdown was not depressed at two sites affected by mine drainage that had concentrations of zinc Ͻ0.5 mg/L and still had shredding stoneflies. For example, invertebrates played a dominant role in litter decomposition in a mountain stream in Alberta, Canada (Mutch and Davies 1984). 11,No.…”
Section: Roles Of Invertebrates and Microbes In Litter Breakdownmentioning
confidence: 99%
“…While further studies report similar results for different leaf species (e.g. Iversen, 1975;Short et al, 1980;Mutch & Davies, 1984), other authors (e.g. Kaushik & Hynes, 1971;Gurtz et al, 1982;Allard & Moreau, 1986) suggest invertebrates are unimportant in leaf decomposition in streams.…”
Section: Fauna1 Dynamicsmentioning
confidence: 67%